Platelet serotonin as a biological marker of autism. - Levy, P Q (1997)
Platelet levels of serotonin were determined by a quantitative direct radioimmunoassay, in a group of autistic patients and a control group. Thirty six autistic patients (28 males and 8 females), all with severe mental retardation, and a group of 23 matched controls, were studied. The serotonin levels in autistic patients (mean +/- SD) (88.37 mmol/dl +/- 40.38) were significantly higher that in the control group (49.54 mmol/dl +/- 16.49). There were no significant differences in levels between the sexes and age groups among subjects in the patient and the control groups. We detected a hyperserotoninaemia in 70% of the autistic patients. We also discuss correlations between serotonin levels in our patients with known aetiologies and levels quoted in the literature and propose RIA to be used as a quick, easy and reliable method for the analysis of large numbers of samples.